2018
DOI: 10.2478/arhss-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Values and Values Based Leadership: What is the Main Focus?

Abstract: The article is based on descriptive theoretical research and focused on two notions such as ‘leadership values’ and ‘values based leadership’. These two concepts are not compared, but every of them is described separately by highlighting general characteristics and showing their broad complexity. Both notions are not related to ethics and / or morality, as the aim the literature review was to provide insights on leadership values and values based leadership. The research question was the following: What aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Leaders have their own set of personal values that will drive their value creation for the organisation (Ertosun & Adiguzel 2018). According to Zydziunaite (2018), there are four principles of value-based leadership: self-reflection, balance, true self-confidence and genuine humility. The competing values of democracy and bureaucracy in the public sector http://www.actacommercii.co.za Open Access environment require leaders to redefine old values to guide employees more effectively (Molina 2009).…”
Section: Organisational Valuesmentioning
confidence: 99%
“…Leaders have their own set of personal values that will drive their value creation for the organisation (Ertosun & Adiguzel 2018). According to Zydziunaite (2018), there are four principles of value-based leadership: self-reflection, balance, true self-confidence and genuine humility. The competing values of democracy and bureaucracy in the public sector http://www.actacommercii.co.za Open Access environment require leaders to redefine old values to guide employees more effectively (Molina 2009).…”
Section: Organisational Valuesmentioning
confidence: 99%
“…He lives by the moral code derived from the Zoroastrian motto, "Good thoughts, good words and good deeds" [8]. The authentic and the ethical persona of Adi helped him to remain humble and grounded, which is a principle on which VBL is based upon (Zydziunaite, 2018). The Godrej Group's core values i.e.…”
Section: Influence Of Adi's Leadership On Godrejmentioning
confidence: 99%
“…Their studies also revealed that leadership skills are founded on the core values of the institution. The outcome may also be connected with the study of Zyziunaite (2018), in which the relationship between the two variables may confirm that Lasallian lay administrators go beyond leveraging and making meaning because they flourish in their careers by boosting their…”
Section: Extent Of Practice Of Lasallian Leadership Based On the Writ...mentioning
confidence: 86%
“…al, 2014; Kaya 2015; Estanislao 2017). If the two ideas are connected the worker does not only focus on leveraging but flourish in their careers by boosting their creativity and productivity (Zyziunaite, 2018). By connecting core values and leadership, the abstract becomes a concrete structure (Baloglu, 2012).…”
Section: B Literature Reviewmentioning
confidence: 99%